The 2-oxoglutarate-dependent dioxygenase superfamily participates in tanshinone production in Salvia miltiorrhiza - Xu, Zhichao (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.